The efficacy of translanguaging as pedagogic practice in selected Namibian multilingual primary classrooms (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This article aims to explore the initial literacy and epistemic benefits of translanguaging as a pedagogic practice in multilingual Namibia. Using notions of recontextualization and translanguaging and classroom observation and data from documents, the article shows how pre-primary teachers and learners draw on heteroglossic repertoires for literacy development and epistemic access. It is argued that this reframes the classroom, not as a site of monolingual epistemic violence, but as a democratic space for initial literacy and epistemic development. The article concludes with an argument for the legitimization of heteroglossic practices in multilingual Namibian classrooms if effective teaching and learning of initial literacy is the goal of basic education